Analisis Efektivitas Persidangan Pidana Secara Elektronik : (Studi di Pengadilan Negeri Kelas II Marisa) - Herlambang Bagus Purnomo; Rustam HS. Akili; Robby W. Amu (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Electronic Trial is a series of processes of examining, adjudicating and deciding the Defendant's case by the Court which is carried out with the support of information and communication technology, audio visual and other electronic means based on the provisions of Supreme Court Regulation (PERMA) Number 4 of 2020 concerning the Administration and Trial of Criminal Cases in Electronic Courts. Carrying out administration and litigation in court through an electronic system to realize the creation of a litigation system that is more orderly, easier and in line with the needs of the times. This electronic court proceeding system is more familiar with the term e-Court. The method used in this writing is empirical juridical with an emphasis on juridical facts obtained by field researchers. The mechanism for conducting electronic hearings is based on the provisions of Article 1 Numbers 11 and 12, including electronic case administration, namely the process of delegating, receiving and numbering cases, determining the day of the hearing, determining the method of the hearing, sending summons/notifications, submitting objection documents, responding to objections, demands. , defense, replica, duplicate, verdict, excerpt of the verdict, sending a copy of the verdict to the Prosecutor and Investigator electronically via the E-court application system. The purpose of establishing electronic trials, known as e-litigation, is to support the effectiveness of a court in adjudicating and examining cases so that they can be effective in accordance with the principles of simple, fast and low-cost justice.